The implementation and efficacy of the responsibility to protect doctrine in contemporary armed conflicts : the case of Gaza - Dyani-Mhango, Ntombizozuko (University of Pretoria, 2025)
Mini Dissertation (LLM (International Humanitarian Law and Human Rights in Military Operations))--University of Pretoria, 2024.